Ocena wpływu ryzyka bankowego na sytuację finansową banku za pomocą analitycznego procesu hierarchicznego - Burzmińska, Justyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The method of analytical hierarchical process (AHP) is a complex procedure which is useful in solving multi-criterion decision-making problems. In case of the assessment of the influence of bank risk on its financial situation, this method has an advantage over other ones on account of the possibility to determine the importance of aims and factors which have an impact on their achievement. Thanks to that the most important factors influencing the position of bank institution is determined. Moreover this method enables in the next stage to classify the individual kinds of risk according to their influence on a problem which is being solved. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 27-35